FRI0212 THE ROLE OF AGE ON THE CLINICAL PRESENTATION AND RELAPSE RATES IN A LARGE COHORT OF 720 PATIENTS WITH GIANT CELL ARTERITIS. (2nd June 2020) - Monti, S.; Dagna, L.; Campochiaro, C.; Tomelleri, A.; Zanframundo, G.; Klersy, C.; Muratore, F.; Boiardi, L.; Padoan, R.; Felicetti, M.; Schiavon, F.; Bond, M.; et al.
Abstract : Background: Giant cell arteritis (GCA) is the most frequent systemic vasculitis after the age of 50 years old. Recent interest in the processes of immune and vascular aging have been proposed as a disease risk factor. Data on the impact of age at diagnosis of GCA on the clinical course of the disease are scarce Objectives: To assess the role of age at diagnosis of GCA on the risk and time to relapse Methods: Centres participating in the Italian Society of Rheumatology Vasculitis Study Group retrospectively enrolled patients with a diagnosis of GCA until December 2019. The cohort was divided in tertiles according to age at diagnosis (≤ 72; 73-79; > 79 years old). Negative binomial regression was used to assess the relapse rate according to age groups, and Cox regression for time to first relapse. Results: Of 720 patients enrolled in 14 Italian reference centres, 711 had complete follow-up data (female 50%; mean age 75±7). Median follow-up duration was 34 months (IQR 16;70). Patients in the older group at diagnosis (> 79 years) had more frequent visual loss compared to the 73-79 and ≤ 72 age groups (31% vs 20% vs 7%; p<0.001), but lower rates of general symptoms (56% vs 70% vs 77%; p<0.001). Large-vessel (LV)-GCA was less frequent in the older group (18% vs 22% vs 43%; p<0.001). At least one relapse occurred in 47% of patients. Median time to relapse was 12 months (IQR 6;23). Age did not influence the rate of relapses [18 per 100 persons/years (95%CI 15;21) vs 19 (95% CI 17;22) vs 19 (95%CI 17;22)], nor the time to first relapse (Figure 1 ). LV-GCA, presentation with significantly elevated c-reactive protein (> 50 mg/L) and general symptoms were independent predictors of relapse. Conclusion: Age at diagnosis of GCA influenced the clinical presentation and risk of ischaemic complications, but did not affect the relapse rate during follow-up. LV-GCA occurred more frequently in younger patients and was an independent predictor of relapse risk, highlighting the need for a correct characterization of the clinical subtype at the early stages of disease. Disclosure of Interests: Sara Monti: None declared, Lorenzo Dagna Grant/research support from: Abbvie, BMS, Celgene, Janssen, MSD, Mundipharma Pharmaceuticals, Novartis, Pfizer, Roche, SG, SOBI, Consultant of: Abbvie, Amgen, Biogen, BMS, Celltrion, Novartis, Pfizer, Roche, SG, and SOBI, Corrado Campochiaro Speakers bureau: Novartis, Pfizer, Roche, GSK, SOBI, Alessandro Tomelleri: None declared, Giovanni Zanframundo: None declared, Catherine Klersy: None declared, Francesco Muratore: None declared, Luigi Boiardi: None declared, Roberto Padoan: None declared, Mara Felicetti: None declared, Franco Schiavon: None declared, Milena Bond: None declared, Alvise Berti: None declared, Roberto Bortolotti: None declared, Carlotta Nannini: None declared, Fabrizio Cantini: None declared, Alessandro Giollo: None declared, Edoardo Conticini: None declared, angelica gattamelata: None declared, Roberta Priori: None declared, Luca Quartuccio Consultant of: Abbvie, Bristol, Speakers bureau: Abbvie, Pfizer, Elena Treppo: None declared, Giacomo Emmi: None declared, Martina Finocchi: None declared, Giulia Cassone: None declared, Ariela Hoxha Speakers bureau: Celgene, UCB, Novartis, Sanofi, Werfen, Rosario Foti Consultant of: lilly, sanofi, MSD, Janssen, Abbvie, BMS, celgene, roche, Speakers bureau: lilly, sanofi, MSD, Janssen, Abbvie, BMS, celgene, roche, Michele Colaci: None declared, Roberto Caporali Consultant of: AbbVie; Gilead Sciences, Inc.; Lilly; Merck Sharp & Dohme; Celgene; Bristol-Myers Squibb; Pfizer; UCB, Speakers bureau: Abbvie; Bristol-Myers Squibb; Celgene; Lilly; Gilead Sciences, Inc; MSD; Pfizer; Roche; UCB, Carlo Salvarani: None declared, Carlomaurizio Montecucco: None declared